Technology of construction and defence of the ukrainian segment of the identifiers’ tree of state informative resources on the basis of risk management - Юдін, Олександр Костянтинович; Бучик, Сергій Степанович (Ukrainian Information Security Research Journal, 2016)
In the article a technology of construction and defence of the Ukrainian segment of the tree of identifiers of state in-formative resources on the basis of risk management is pre-sented for the first time. This technology is based on re-searches that were conducted by the authors before and are related to the first worked out methodology of construc-tion of a classifier of threats to the state informative re-sources; to the conducted analysis of the world tree of iden-tifiers of informative resources and to the place of the Ukrainian segment of identifiers of objects in it; to the structural-logical model of organization of hierarchical branch of codes-knots of the Ukrainian segment of identi-fiers of objects of public organs; to models and principles of informative safety worked out by the authors, methods and models of realization of control system of informative safety of the state informative resources; to worked out theoretical bases and methodology of analysis of risks of the tree of identifiers of state informative resources, to other works that are bound by the only aim - the develop-ment of the methodology of construction and defence of the Ukrainian segment of the tree of identifiers of the state informative resources. Introduction of this technology must become a unifying factor for generalization of expe-rience of construction of defence of the state informative resources in the country on the basis of risk management and approaches that do not conflict with international standards.